Pelatihan Manajemen Pariwisata dan Ekonomi Kreatif di Kabupaten Bandung: (Tourism Management and Creative Economy Training in Bandung Regency) - Agustina Setiawan; Titin Rohayatin; Iing Nurdin; Widuri Wulandari Wulan (Sam Ratulangi University, 2024)
Villages in Bandung Regency have the opportunity to realize tourism management and a creative economy. However, until now not all villages in Bandung Regency have been able to make this happen. This training aims to increase the knowledge of village government officials in tourism management and the creative economy. The implementation method is by providing material on tourism management and the creative economy, management training and workshops on tourism management and the creative economy, and Focus Group Discussions (FGD) with village government officials related to tourism management and the creative economy throughout Bandung Regency. As a result of the FGD, it was found that there are still several villages that have potential but have not been able to develop into tourist villages or realize a creative economy. This is due to the limited budget, knowledge, and infrastructure of the village. For this reason, further training is needed on the same theme. Keywords: Management; Creative Economy; Village Government Keywords: Management; Creative Economy; Village Government ABSTRAK Desa yang ada di Kabupaten Bandung memiliki peluang untuk mewujudkan manajemen pengelolaan pariwisata dan ekonomi kreatif. Namun, sampai saat ini belum seluruhnya desa di Kabupaten Bandung dapat mewujudkannya. Pelatihan ini bertujuan untuk meningkatkan pengetahuan aparatur pemerintah desa dalam manajemen pariwisata dan ekonomi kreatif. Metode pelaksanaan yaitu dengan cara pemberian materi tentang manajemen pariwisata dan ekonomi kreatif, pelatihan pengelolaan/ workshop manajemen pariwisata dan ekonomi kreatif dan Focus Group Discussion (FGD) dengan para aparatur pemerintah Desa terkait manajemen pariwisata dan ekonomi kreatif se-Kabupaten Bandung. Hasil dari FGD, ditemukan masih ada beberapa desa yang memiliki potensi, namun belum mampu untuk dikembangkan menjadi desa wisata, ataupun mewujudkan ekonomi kreatif. Hal ini dikarenakan keterbatasan anggaran, pengetahuan, dan infrastruktur dari desa. Untuk itu, diperlukan pelatihan lanjutkan dengan tema yang sama.